- #1

- 3

- 0

Find

**dy/dx**for the following:

**y = (5e^(2+ix))/(3e^(1-2ix))**

- Thread starter tracey163
- Start date

- #1

- 3

- 0

Find

- #2

- 3

- 0

- #3

- 3

- 0

(Quotient rule)

dy/dx = ((5ie^(2 + ix))(3e^(1-2x)) - (-6ie^(1 - 2ix))(5e^(2 + ix))) / ((3e^(1 - 2ix))^2)

= (15ie^(3 - ix) + 30ie^(3 - ix)) / (9(e^(1 - 2ix))^2)

= (45ie^(3 - ix)) / (9(e^91 - 2ix)^2)

= (5ie^(3 - ix)) / ((e^(1 - 2ix))^2)

And I'm not sure where to go from there its either wrong or it needs simplifying some more...

- #4

- 3

- 0

y = 5/3.e^(2 + ix - (1 - 2ix))

=5/3.e^(1 + 3ix)

dy/dx = 5ie^(1 + 3ix)

:D thanks!

- #5

- 3

- 0

You're welcome :-)

- Last Post

- Replies
- 11

- Views
- 7K

- Replies
- 5

- Views
- 2K